Essential findings from long term conditioning support for female athlete - Iwamoto, S.; Ota, M.; Oue, A.; Okuma, H.; Kubota, Y.; Terada, N.; Kawaguchi, N.; Suzuki, T.; Sugita, K. (Journal of High Performance Sport, 2019)
This report presented the outline of the continuous conditioning support system for newly formed college female long distance team and in response to anemia as health problem. All participants belong to college female long distance team whose breakfast and dinner are serve at the university dormitory. The conditioning support system is divided three parts. At the first stage, self-checks are conducted by the athletes; the primary check for technical, medical, physical, nutritional and psychological are in the second stage; specialized institutions such as medical facility and treatment centers conducted outside the university for the third stage.The conditioning application (ASU-Log) was used by the athlete`s self - checks. The system engineer was in charge of the management of the system. Coaches were responsible for checking athletes` performances and adjusting the practice contents (quality and quantity). While the doctor and the athletic trainer are in charge of checking health problems (including orthopedic). And if problem occurs, referred to the specialized facilities the third stage. Athletic trainers teach re-conditioning plans. Physiologists is in charge of measuring the maximum oxygen uptake, conditioning coach is in charge of physical strength measurements and instruct physical training. Dietitian managed nutrition by creating daily menus and checking meal contents. Mental consultations were provided by psychiatrist. In addition, a conditioning education program was used for the athletes. The competition results indicated that team has gradually improved. However, it took time to solve the anemia addressed as a health problem. In order to make the conditioning support system function flawlessly at the sports field, it is necessary to construct a system particularly focused on athletes and the sports. In addition, continuous observation for athletes as individuals are recommended.